2005
DOI: 10.1177/108471380500900203
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Dynamic Range Optimization (ADRO): A Digital Amplification Strategy for Hearing Aids and Cochlear Implants

Abstract: Adaptive dynamic range optimization (ADRO) is an amplification strategy that uses digital signal processing techniques to improve the audibility, comfort, and intelligibility of sounds for people who use cochlear implants and/or hearing aids. The strategy uses statistical analysis to select the most information-rich section of the input dynamic range in multiplefrequency channels. Fuzzy logic rules control the gain in each frequency channel so that the selected section of the dynamic range is presented at an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 41 publications
3
68
0
5
Order By: Relevance
“…The ADRO strategy was initially developed for bimodal listening and has been previously validated for hearing aids and cochlear implants (Blamey, 2005). Studies by James et al (2002) and Dawson et al (2004) concluded that sound quality and speech perception performance were improved using ADRO as compared to fixed channel gains in both adults and children.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADRO strategy was initially developed for bimodal listening and has been previously validated for hearing aids and cochlear implants (Blamey, 2005). Studies by James et al (2002) and Dawson et al (2004) concluded that sound quality and speech perception performance were improved using ADRO as compared to fixed channel gains in both adults and children.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…b) Also at School of Behavioral and Brain Sciences, The University of Texas at Dallas,Richardson,Texas 75080. aids (HA) (Blamey et al, 1999;Blamey, 2005). The strategy uses statistical analysis to select the most information-rich section of the input dynamic range in multiple frequency channels, and adaptively adjusts the channel gains based on a set of fuzzy logic rules to optimally place the signal in the users' available hearing range.…”
Section: Introductionmentioning
confidence: 99%
“…Some hearing aids incorporate AGC with multiple time constants [63,64] or time constants that adapt depending on the characteristics of the signal [65]. Such systems are generally designed so that they are slow-acting most of the time.…”
Section: Multiple or Adaptive Time Constantsmentioning
confidence: 99%
“…ASC shifts the IIDR up in acoustical level if the estimated background noise level exceeds a certain threshold, and shifts the IIDR down when background noise drops below a lower threshold. ADRO analyzes the average and peak envelope levels and the background noise and adjusts the gain of individual frequency channels to maintain a comfortable loudness perception in each channel (Blamey, 2005;Khing et al, 2013). By adjusting the gain of individual frequency channels, ADRO influences both the selection of the frequency channels for stimulation as well as the stimulation levels with which the selected frequency channels are stimulated.…”
Section: Influence Of Adro On the Effect Of Amf Adjustments On Speechmentioning
confidence: 99%